Die Wenslikheid van Afrikaans as Vaktaal vir Regstudent - Lombard, Ellen; Carney, Terrence R (Potchefstroom electronic law journal, 2017)
Since 1994 the official language status in South Africa went from two state languages to eleven. This caused English to stand out as the lingua franca of the wider community and resulted in government using English as the preferred medium of communication. This is especially the case in the business of law. The legal practice from the private, public and academic sectors is anglicising at a rapid rate which means that Afrikaans is diminishing as a legal language and that the nine additional official languages are not being developed entirely to function at a higher level. In the light of Anglicisation it begs the question whether it is still useful to teach Afrikaans as a legal language at tertiary institutions. This article explores the matter by focusing on the following: the importance of language within the legal profession, the history of Regsafrikaans, Anglicisation within the legal profession, English as the only language of record and the expediency of Afrikaans as a legal language. The authors arrive at the conclusion that it is indeed still important to teach Regsafrikaans to law students and recommend that law faculties should keep or reinstate this subject as part of their LLB curriculum.